2012
DOI: 10.1016/j.jksus.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Breeding, embryonic development and salinity tolerance of Skunk clownfish Amphiprion akallopisos

Abstract: Breeding and rearing some of the clownfishes most commonly used in the aquarium trade actually represent an economical and ecological tool for broadening development. Culture of clownfish species in low-saline water is still in its infancy. Salinity of the culture environment is one of the more relevant parameters affecting fish physiology, modifying food intake and growth performance in many fish species. The objective of this study was to breed skunk clownfish (Amphiprion akallopisos) in aquarium condition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
(23 reference statements)
2
18
0
2
Order By: Relevance
“…Growth analysis of cinnamon clownfish at salinities of 34 ppt, 25 ppt, 15 ppt, and 10 ppt indicated that A. melanopus could survive at salinities as low as 10 ppt over a period of 90 days. The result is similar to that of skunk clownfish A. akallopisos with high survival rates under the condition of salinities up to 53 ppt and tolerance up to 6 ppt of salinity [10]. Lower survival rates of A. melanopus at lower salinities were inconsistent with the previous studies examining the relationship between growth and salinity in juvenile black bream [11].…”
Section: Discussionsupporting
confidence: 57%
“…Growth analysis of cinnamon clownfish at salinities of 34 ppt, 25 ppt, 15 ppt, and 10 ppt indicated that A. melanopus could survive at salinities as low as 10 ppt over a period of 90 days. The result is similar to that of skunk clownfish A. akallopisos with high survival rates under the condition of salinities up to 53 ppt and tolerance up to 6 ppt of salinity [10]. Lower survival rates of A. melanopus at lower salinities were inconsistent with the previous studies examining the relationship between growth and salinity in juvenile black bream [11].…”
Section: Discussionsupporting
confidence: 57%
“…Berbeda dengan ikan hias clown hitam (Amphiprion percula) yang memiliki bentuk lonjong dengan kisaran ukuran yang relatif lebih besar dari telur ikan letter six dengan ukuran 2,21 x 0,89 mm (Kusumawati & Setiawati, 2010). Sedangkan pada ikan clown biasa (Amphiprion ocellaris) memiliki bentuk lonjong dengan ukuran 1,8 x 0,8 mm (Yasir & Qin, 2007), sementara itu, pada jenis ikan clown lainnya yaitu Amphiprion akallopisos memiliki kisaran ukuran 2,21 x 1 mm (Dhaneesh et al, 2011). Pada ikan hias lainnya yaitu dari jenis ikan goby (Priolepis nocturna) memiliki bentuk oval dengan ukuran lebih besar dari ukuran telur ikan letter six yaitu 0,82 x 0,51 mm (Wittenrich et al, 2007).…”
Section: Hasil Dan Bahasan Pemijahan Induk Dan Perkembangan Embriounclassified
“…Durasi perkembangan embrio ikan letter six terjadi dalam waktu 22 jam 24 menit (Tabel 1). Dalam kondisi suhu air yang sama yaitu berkisar 27°C-28°C, perkembangan embrio ikan letter six relatif lebih cepat jika dibandingkan dengan ikan hias laut dari jenis Amphiprion di mana pada ikan A. ocellaris dan A. kallopisos memerlukan waktu yang sangat lama yaitu 152 jam (Yasir & Qin, 2007;Dhaneesh et al, 2011). Sedangkan pada ikan jenis goby (Priolepis nocturna) memerlukan waktu 96 jam untuk larva bisa menetas (Wittenrich et al, 2007).…”
Section: Hasil Dan Bahasan Pemijahan Induk Dan Perkembangan Embriounclassified
“…To preserve the delicate reef ecosystem, many studies have been carried out to develop breeding and rearing methods for marine ornamental fi shes, which are essential to the development of sustainable ornamental aquaculture (Ajith Kumar and Balasubramanian, 2009;Ajith Kumar et al, 2010;Dhaneesh et al, 2011). However, information regarding the breeding of clownfi shes in brackishwater is limited.…”
Section: Introductionmentioning
confidence: 99%